Pengaruh Aerobic Exercise Terhadap Nyeri Menstruasi Pada Siswi SMPN 35 Bekasi Tahun 2018 - Berbudi B L, Abdurahman; Fitria, Dora (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2021)
Background: There are many things that occur in adolescents related to menstruation, pain due to menstruation, and stress due to a period of development that can interfere with the physical activity of teenagers. Physical activity carried out is a sport to overcome the problem, namely aerobic exercise. The design of this study is pre-experimental. The total sample of 21 people was chosen by purposive sampling technique. Data collection is done by measuring menstrual pain and interviews. Data analysis included univariate analysis and bivariate analysis using parametric Paired Sample T-Test. Results: Mean for pain value of 6.38 before intervention and 4.28 after intervention. The statistical test obtained a value of p = 0.001 which means that there was a significant decrease in pain during menstruation. Conclusion: Aerobic exercise can significantly reduce menstrual pain. Teenagers can do aerobic exercise regularly to reduce menstrual pain.